O De Consulatu Suo de Marco Túlio Cícero frente às tradições poéticas romanas - Oliveira, Alessandro Carvalho da Silva (2023)
In this thesis, we identify the discursive strategies of Marcus Tullius Cicero, in his poetic corpus, through which he disputed his social position, both in the context of writing his poems, and later, when fragments of them appear in other works, especially the philosophical ones. We take into consideration, among other issues, intertexts and the link to a construction of Roman identity based on the appropriation of collective themes, such as those treated by constituent discourses, which could help create the poet's discursive authority. In the last century of the Roman Republic, territorial expansion caused a diverse cultural circulation, modifying the Discursive Universe in which Cicero was present. Being an orator and homo nouus, happropriated elements of these new discourses to promote his political career in multiple ways; literature being one of them. His poems always approached matters of public interest, such as religion, politics and history, but sometimes their main object was the lives of some individuals, such as Marius — the orator's famous general compatriot — and himself. We observed how both the publication of written versions of the speeches given as a speaker, and these narratives in verse with an autobiographical content are ways of constructing auctoritas, consolidating a legitimacy to occupy spaces that are not commonly accessible to homines noui who were not successful in military careers. The poem to which we pay the most attention in this thesis is De Consulatu Suo, whose reception was already predominantly negative both in the period when Cicero was still alive and in the Principate. The choice to highlight this specific work was due to the gap in research on this source, considering the attention given to the orator's prose works. We deal with the possibilities of autobiography in Cicero, investigating in the epistles and forensic speeches ways in which we can observe attempts at self-promotion, even though they could be frowned upon in the discursive universe of the Roman Republic. Subsequently, we locate the speaker in the history of literate practices in Rome, highlighting both the context in which his verses were produced and the possible authors with whom Cicero could obtain advantages by associating himself. Finally, we analyzed the poems, providing a translation of them and concluded that, although the appropriation of themes and authors before him were fundamental, Cicero carried out an essentially experimental activity in his poetic project, resulting in a strange feeling for later readers, but providing a reflection on ways of thinking about inventive potential in the literate practices of the Roman Republic